Four new spider species of Cubanops Sánchez-Ruiz, Platnick & Dupérré from Eastern Cuba (Araneae: Caponiidae) - Sánchez-Ruiz, Alexander; Bonaldo, Alexandre B. (Zootaxa, 2024)
Four new species of Cubanops are described from Eastern Cuba: C. chamarreta sp. nov. (male and female), C. glochidiosus sp. nov. (male and female), C. guama sp. nov. (male and female) and C. serrucho sp. nov. (male). Also, an updated distribution map for all nine Cubanops species known from Eastern Cuba is included.